Epidemiology of hepatitis B in Portugal. Issue 3 (March 2017) - Silva, Mário J.; Valente, João; Capela, Tiago; Russo, Pedro; Calinas, Filipe
Abstract : The epidemiology of hepatitis B in Portugal is insufficiently characterized. We aimed to review the epidemiology of hepatitis B in Portugal since 1980. A literature review was performed in MEDLINE, Scielo, Web of Science, and the Portuguese Scientific Repository for studies containing 'Hepatitis B' and 'Portugal' published from 1980 to June 2016. The initial search was complemented by abstract books from national gastroenterology and hepatology meetings and reports from the Service for Intervention on Addictive Behaviours and Dependences, the Portuguese Blood Institute, and Directorate-General of Health. Further studies were identified in references of retrieved papers andhttps://www.google.pt . Ninety references were included. Hepatitis B surface antigen (HBsAg) prevalence was up to 2% in the general population and decreased in the last decades: 1.13–2.0% in studies carried out in 1980–1989 and 0.02–1.45% in studies carried out in 1990–2014. Among pregnant women, HBsAg prevalence was 1.35% in those on primary care, but 6.2% among risk parturients. Among drug abusers, HBsAg prevalence decreased from 10–19.6% in the decades of 1980–1990 to 4.8% in 2014. Higher HBsAg prevalence rates were observed among populations of African or Asian origin. Individuals with hepatitis B were mostly men, mean age 36.9–49 years. The most frequent viral genotype was D. Genotype E is more prevalent in patient cohorts from Central-Southern Portugal (10–62%) than those from Northern Portugal (1–4.1%). The proportion of inactive carriers varied from 24.2 to 73%. The prevalence of cirrhosis varied from 5.8 to 23.7%. Portugal is a low-endemicity country for hepatitis B. Nevertheless, prevalence is high among specific subgroups that may benefit from specifically designed healthcare programs.